THE EFFECTIVENESS OF INTEGRATED WRITING TECHNIQUE IN TEACHING WRITING JOB APPLICATION LETTER TO THE TWELFTH GRADERS OF VOCATIONAL HIGH SCHOOL (RETAIN, 2014)
THE EFFECTIVENESS OF INTEGRATED WRITING TECHNIQUE IN TEACHING WRITING JOB APPLICATION LETTER TO THE TWELFTH GRADERS OF VOCATIONAL HIGH SCHOOL YUNI YULIANTI S1-Pendidikan Bahasa Inggris, Fakultas Bahasa dan Seni, Universitas Negeri Surabaya e-mail: yuniyuliantibisa@gmail.com Pembimbing: Him’mawan Adi Nugroho, S.Pd.,M.Pd. Dosen Jurusan Bahasa Inggris, Fakultas Bahasa dan Seni, Universitas Negeri Surabaya e-mail: himmawanadi@englishunesa.com. Abstrak Penelitian ini bertujuan untuk mengetahui apakah ada perbedaan yang signifikan dalam hasil belajar menulis surat lamaran pekerjaan antara siswa yang diajar dengan Teknik Menulis Terpadu dan mereka yang tidak. Peneliti melakukan penelitian ini pada siswa kelas dua belas diSMK Negeri 1 Grati - Pasuruan. Penelitian ini menggunakan metode penelitian eksperimen dengan menggunakan dua kelompok sampel yaitu kelompok eksperimental dan kelompok kontrol. Data yang diperoleh dari penelitian dianalisis dengan menggunakan prosedur Independent - sampel t -test dan Paired - sampel t -test di SPSS. Hasil analisis dari penelitian menjelaskan bahwa Teknik Menulis Terpadu efektif dalam meningkatkan nilai menulis siswa dalam kelompok eksperimen, karena skor total tulisan siswa di kelompok eksperimen mengalami peningkatan dengan kekuatan kenaikan skor sebesar (0,52) eta squared menunjukkan efek peningkatan yang sangat besar, lebih tinggi dari kenaikan total skor tulisan siswa di kelompok kontrol yang hanya mengalami peningkatan sebesar (0,14) eta squared. Dalam aspek isi, skor menulis siswa pada kelompok eksperimen meningkat dengan peningkatan sebesar (0,33) eta squared (sangat besar ), dalam aspek organisasi meningkat dengan besarnya peningkatan (0,43) eta squared (sangat besar ), dan dalam aspek kosakata meningkat dengan besarnya peningkatan (0,18) eta squared (besar). Peningkatan – peningkatan tersebut lebih tinggi dari peningkatan skor siswa dalam kelompok kontrol yang hanya sebesar (0,05) eta squared dalam aspek isi, (0,16) eta squared dalam aspek organisasi, dan (.0,01) eta squared dalam aspek kosakata. Namun, dalam aspek tata bahasa, peningkatan skor kelompok eksperimen hanya sebesar (0,17) eta squared lebih rendah dibandingkan peningkatan kelompok kontrol yang sebesar (0,41) eta squared. Kemudian, dalam aspek mekanik, tidak ada peningkatan, tetapi terjadi penurunan dengan besarnya penurunan (0,006) eta squared. Akhirnya, diperoleh beberapa kesimpulan bahwa Teknik Menulis Terpadu lebih efektif daripada teknik konvensional dalam mengajar menulis surat lamaran pekerjaan, yang dapat meningkatkan skor menulis siswa dalam aspek isi, organisasi, dan kosa kata. Namun, dalam aspek tata bahasa, teknik konvensional dianggap lebih efektif daripada Teknik Menulis Terpadu. Kemudian, Teknik Menulis Terpadu juga dianggap tidak efektif dalam mengajarkan menulis surat lamaran pekerjaan untuk meningkatkan skor siswa dalam aspek mekanika. Kata Kunci: Teknik Menulis Terpadu, Hasil Belajar Siswa, Menulis Surat Lamaran Kerja. Abstract This study was aimed to find out whether there is significant difference in learning outcomes of writing job application letter between students who are taught by integrated writing technique and those who are not. The researcher conducted this study to the twelfth graders of SMK Negeri 1 Grati – Pasuruan. This study used experimental research method with two groups designed called experimental group and control group. Then, the data obtained from the research were analyzed by using Independent – samples t-test and Paired – samples t-test procedures in SPSS. The result of this study explained that Integrated Writing Technique is effective in improving the students in experimental group writing scores since the students’ composition total scores of experimental group was getting increase with magnitude of increase (.52) eta squared indicates very large effect size, higher than the increase of control group’s composition total score which only has magnitude of increase (.14) eta squared indicates large effect size. In term of content, the students writing scores in experimental group increased with magnitude of improvement (.33) eta squared (very large effect size), in term of organization increased with magnitude of improvement (.43) eta squared (very large effect size), and in term of vocabulary increased with magnitude of improvement (.18) eta squared (large effect size). Those improvements are higher than the improvement of students’ scores in control group which only (.05) eta squared in term of content, (.16) eta squared in term of organization, and (.01) in term of vocabulary. However, in term of language use, the improvement of experimental group scores is only (.17) eta square lower than control group’s which is (.41) eta square. Then, in term of mechanics, there is no improvement, but reduction with magnitude of decrease (.006) eta square. Finally, it is gained some conclusions that Integrated Writing Technique is more effective than conventional way in teaching job application letter, which can improve the students’ writing skill in term of content, organization, and vocabulary. However, it is considered that conventional way is more effective than Integrated Writing Technique in term of language use. Then, it is considered that Integrated Writing Technique is not effective in teaching job application letter in term of mechanics. Keywords: Integrated Writing Technique, Learning Outcomes, Writing Job Application Letter. INTRODUCTION In language learning, writing is an important language skill that must be mastered by students who learn language. Moreover, for vocational high school students who learn English for specific purpose which will be needed in their work place, writing as a key method of communication for most people, become more important for them to master and struggle. Although writing and communication skills have degraded since the development of technology in which more and more people communicate through email and text messaging, developing writing skills is still important in the business world to create business letter. So that, creating job application letter especially for vocational school students is still also important. The importance of teaching and learning writing as a key method of communication is stated on Standar Isi SMK/MAK (BSNP, 2006). English subject is taught to vocational high school students as adaptive subject to improve the students communication skills that will be needed in their vocational program and in further work place. For the twelfth graders, it is hoped that the students are able to communicate using English in intermediate level both oral and written. One of that expected skills is writing bussiness letter includes job application letter that will be needed by the students to apply for a job. Unfortunately, writing is not an easy skill for both EFL (English as a Foreign Language) teachers and learners since English is not their first language. Morover, learning writing contains some issues that must be learned. As Rass (2001), stated that writing is a difficult skill for both native speakers and nonnative speakers alike, because authors must balance multiple issues such as content, organization, purpose, audience, vocabulary, punctuation, spelling, and mechanics such as capitalization. Zheng (1999) in Yan (2005), stated that acquiring the writing skill seems to be more laborious and demanding than acquiring the other three skills (reading, listening, and speaking). Madsen (1983: 101) added that there are many factors must be considered in writing such as mechanics (including spelling and punctuation), vocabulary, grammar, appropriate content, diction, rhetorical matters of various kinds (organization, cohesion, unity; appropriateness to the audience, topic, and occasion); as well as sophisticated concerns such as logic and style. So that, many of teachers and students face certain problems in teaching and learning writing as English as Foreign Language (ESL); included writing job application letter. Therefore, since the importance of the skillfulness of writing job application letter for vocational high school students, it is needed many kinds of methods, techniques or strategies to teach it. Among some techniques of writing, there is a good technique to teach writing which is introduced by Cecilia B-Ikeguchi (1997). The technique is called integrated writing technique. Integrated Writing Technique is a technique of teaching writing that integrates some skills; those are speaking, listening, reading, and writing. In the teaching and learning activity, those four skills are combined and are divided into three phases; those are assignment phase, interactive phase, and writing phase. Indeed, students‘ writing composition will be the product in the end of the teaching and learning activity. As Ikeguchi (1997) explained that in Integrated Writing Technique, there are three phases; those are assignment phase, interactive phase, and writing phase. First phase of the lesson begins one week before teaching and learning process with the giving of the assignment. In this assignment phase, the students have to choose any topic that they are most interested in. Then, they have to look for a short magazine or newspaper article, read it thoroughly until they understand the content, and make a copy to bring to class. Next, the second phase is interactive phase which begins in the next meeting, the students in the same topic take turns in reading or reporting each of their articles to the group members. While, everybody else listens and then asks questions to clarify points that are unclear, or make comments. Finally, in writing phase, the students have to write about two things: (1) the topic they had chosen to read and to bring to class, and (2) the other related aspects of the same topic that they found out from the group interaction. In teaching writing job application letter, the implementation of integrated writing technique was as follow; in assignment phase, teacher wrote on the white board a list of some job field which the teacher thought would attract the students to apply. The teacher allowed each of the students to choose one job field that they were most interested in. Then, the teacher asked them to look for a job vacancy advertisement dealing with the job field that each of them had chosen from newspapers or internet, then read the job vacancy advertisement thoroughly until they understood the requirements of it, and made a copy of it, then brought it to class in the next meeting. In the interactive phase which was started in the next meeting, the teacher explained about job application letter; what it is, what its structures are, and what its contains are. After giving explanation, teacher asked the students who had chosen the same job field to sit together and form a group of four. Then, the teacher asked the students within the same group to take turns in reading -or reporting- each of their job vacancy advertisement to the group members. While, everybody else listened and then asked questions to clarify points that were unclear, or gave comments. Its aim was to recognize job requirements relating to the job field, so that they could think of their needed qualification in order to be able to apply for the job. Then, the teacher gave each group two examples of job application letter to be discussed and identified their structures based on the teacher’s explanation. The teacher allowed as much time as the students are willing to talk, or half of the whole class time. The students are required to understand about the job application letter well. In writing phase, the teacher asked the students to get back to their seats, and asked them to summarize the applicants’ requirements which is required in the job vacancy advertisement that they brought to the class, and outlined or wrote their curriculum vitae (included their personal and contact information, qualifications (education), experiences (work history and fields of interest), and their awards (professional membership, courses, and professional qualification) based on the requirements on the job vacancy advertisement in several sentences in a paragraph. Besides, they were also asked to express their personal opinion or belief toward the job vacancy based on their qualification that they can fill the mentioned carreer position in a paragraph. Finally, in the last meeting, the teacher asked each of the students to compose a job application letter by developing their outline they had already made in the previous meeting. Due to the goodness of Integrated Writing Technique above, the researcher thought that it would be helpful to cope the teaching problem in SMK Negeri 1 Grati Pasuruan. It is since when the teachers taught the twelfth graders writing job application letter through conventional way, the students commonly copied the content and sentences of the sample of job application letter given when they were asked to compose their own job application letter. Meanwhile, job application letter must reflect the applicant's personality in a positive way and includes basic information about job applicant’s expertise and qualifications. It should reflect job applicant’s enthusiasm and competency for the job. As Kurniawan (2008) stated that job application letter’s main objective is to get the applicant in the door for an interview and must be written well enough to attract the attention and interest of the person who has power to recommend the applicants. If the students learn to write job application letter, they must be able to state positive arguments about their own personality and personal information toward their appropriateness to the job, not by copying the sample of job application letter given. Therefore, since in Integrated writing technique there are activities which require students to be creative in expressing their personal opinion or beliefe, it is hoped that this technique will be effective in improving the students’ skill in writing good job application letter, and minimize the copying which is commonly done by the students. For those reasons, the researcher was eager to do this research in SMK Negeri 1 Grati - Pasuruan in order to know know whether this writing technique would be effective to improve the students learning outcomes of writing job application letter or not. In order to know the improvement of the students learning outcomes, the reasearch question of this study was whether there is significant difference in the scores of writing job application letter between students who are taught by integrated writing technique and those who are not. RESEARCH METHODOLOGY Research Design This study used Experimental Research design since this study investigated the effectiveness of Integrated Writing Technique in teaching English in Indonesian context especially in improving the students learning outcomes in writing job application letter. It is in line with the statement stated by Ary et al. (2010:265) that experimental research is a scientific investigation in which the researcher manipulates one or more independent variables, controls any other relevant variables, and observes the effect of manipulations on the dependent variables. In this study, the researcher aimed to find how successful integrated writing technique in improving the students learning outcomes. It is investigated by comparing the improvement of students scores in writing job application letter in term of content, organization, vocabulary, mechanics, and language use, between the students who were taught by using integrated writing technique and those who were not. There were two groups of sample used in this study; those were experimental group and control group. The experimental group was expected to give the influence of the independent variable to the dependent variable, while the control group was not. Firstly, both experimental and control groups were given Pre-test in order to measure their ability in writing application letter. Then, treatment was given to the experimental group. After that, the treatment was examined through a post-test that was administered to both groups. Research Variables There were two variables in this study. They were independent variable and dependent variable. Marczyk, G et al. (2005:42) stated that “the independent variable is the factor that is manipulated or controlled by the researcher”. In this case the independent variable of this study was Integrated Writing Technique. In addition, Marczyk, G et al. (2005:44) added that “the dependent variable is a measure of the effect (if any) of the independent variable”. The dependent variable of this research was the students’ ability in writing job application letter. Population and Sample Ary et al. (2010: 148-149) stated that population is all members of any well-defined class of people, events, or objects in a large group to which the researcher wishes to generalize the the results of the study. In this study, the population was the twelfth graders of SMK Negeri 1 Grati Pasuruan, that was divided into 14 classes; those are XII AK 1, XII AK 2, XII KI 1, XII KI 2, XII TPM 1, XII TPM 2, XII TPc 1, XII TPc 2, XII TAV 1, XII TAV 2, XII ATUg, XII API, XII MM 1, and XII MM 2. Ary et al. (2010: 148-158) also explained about sample and sampling techniques. Sample is a small group as a part of a population that is observed. To determine the sample, there are two types of sampling that might be used; they are probability sampling and non probability sampling. In probability sampling, the methods of sampling are simple random sampling, stratified random sampling, cluster random sampling, and systematic sampling. While in non probability sampling, the methods of sampling are accidental sampling, purposive sampling, and quota sampling. In this study, the researcher used purposive sampling technique, since the researcher selected the sample from population with a particular reason. (Ary et al, : 2010). In this study, the researcher determined two sample classes from population by a certain purpose; that is to choose two classes which has similar ability in learning English. It aimed in order to ease the teaching and learning process, and also to keep the validity of data. After getting the sample, the researcher determined the experimental group and the control group randomly. Thus, the researcher used a tossing coin to decide which group would get the treatment. The two sample classes were chosen from 14 classes of population by a certain purpose. Based on the information from the teacher, the learning ability of both XII KI 1 and XII KI 2 are not too different, and the ability of the students in the both classes are various. Thus, the researcher decided to choose them as samples in this study. Then the researcher chosed which class would get the treatment randomly by tossing coin. Finally, the result was XII KI 2 as an experimental group which was given the treatment, and XII KI 1 as the control group which was not given the treatment. Instrument In collecting data, the researcher used an instrument as the device to get the data needed. The instrument which is used in this study was a test. “A test is a set of stimuli presented to an individual in order to elicit responses on the basis of which a numerical score can be assigned. This scores, based on a representative sample of the individual’s behavior, is an indicator of the extent to which the subject has the characteristic being measured.” (Ary, et. al, 2010: 201). Tests that are widely used in educational research, such as this study, are achievement tests. Also based on (Ary, et.al, 2010: 201), there are five kinds of achievement tests; those are standardized tests, researcher – made tests, norm – referenced and criterion – referenced tests, test performance range, and performance assessment. In this study, the researcher used researcher – made test, so that the researcher could suit the test with the specific objectives of this study, it means that the test was hoped could match more closely with the content that was covered in this study. Madsen (1983:5) stated that tests is an important part of every teaching and learning experience that can provide insights into ways that can improve the evaluation process and also help us answer the important questions. So that, a test in this study was writing test which is important to answer the research questions about the effect of using Integrated Writing Technique as a technique for teaching writing job application letter to the twelfth graders of SMK Negeri 1 Grati - Pasuruan. In this study, the test was in the form of composition test. The test was administered twice; those were pre-test and post-test. Pre-test was administered first in order to assess the students‘ writing ability before the treatments, while post-test was administered next after the treatments in order to assess the students‘ writing ability after the given treatments. Pre-test and post-test were given to the both groups; experimental and control groups. The form of composition test was chosen in this study since it only required short time to construct and it was considered able to be the way to measure the students‘ writing ability directly. In this case, the composition test was composing a job application letter. The students were given 45 minutes to do the test. The instruction of the composition that should be composed by them in pre-test was the same as the instruction of the composition that should be composed by them in post-test. The instruction was ― Write an application letter to apply for a job based on job vacancy advertisement given. Before the real application of pre-test and post-test, the researcher conducted tryout. The purpose of tryout was to enable the researcher to get the appropriate test item that is suitable for the students’ level and also to get validity and reliability. Morover, it also gave the researcher an idea about the time allocation for the students to do the test. In this tryout, the test was in the form of composition test. It was given to the group which does not belong to both experimental group and control group. In this study, tryout was conducted before doing pre-test to the experimental and control group; the researcher conducted tryout on Tuesday, 19th of November 2013 in the 7th period of lesson to the students of XII AK 2. In this tryout, the students was asked to compose a job application letter with the instruction “Write an application letter to apply for a job based on job vacancy advertisement given.” The result of tryout showed that the test instrument was valid and reliable that is presented in the following explanation. Validity of Tryout Test Instrument The test that was given to the students should be valid. A test will valid if it can successfully measure what will be intended to measure. As explaine before, that the tryout was conducted before conducting pre – test and post - test in order to examine the test as an instrument. One of things that must be examined is the validity of the test. Validity is the most important consideration in developing and evaluating measuring instruments. Ary et.al, (2010: 224), defined validity as the extent to which scores on a test enable one to make meaningful and appropriate interpretations. Then, he explained that there are three types of validity; those are content validity, criterion – related validity, and construct validity. In this study, the researcher used content validity, as consideration that content validity relates to the consistency of the test with its objective (Susanto, 2000: 17). Content validity was used to examine the content of the test. The test should representatively contain the item that supposed to be measured. So, content validity was gained by mapping the test item with the objectives stated in the curriculum; that Vocational High School students in the twelfth grade are expected to be able to write bussiness letters include a job application letter. ( BSNP: 2006). Thus, the item in the test must represent the objective that stated in the curriculum. The result of analysis toward the test considered that the test instrument was valid. It is since the test item which asked the students to write their own job application letter based on the job vacancy advertisement given, is relevant to the learning objectives stated in the curriculum. The learning objectives are; students are able to understand the parts of application letter, students are able to understand the content of application letter, students are able to understand an advertisements on job vacancies, and students are able to compose job application letters to respond job vacancy advertisement. Reliability of Tryout Test Instrument Besides examining the validity, the researcher also examined the reliability of the test since it is also an important element to measure the quality of the test. Reliability indicates how consistently a test measures whatever it does measure. To be able to make valid inferences from a test’s score, the test must first be consistent in measuring whatever is being measured. (Ary, et.al., 2010: 239). There are some general types of reliability; those are inter-rater reliability, test – retest reliability, internal consistency, and inter method reliability. In this study, the reliability of the test was examined by using inter – rater reliability. It means that one test was administered once and it was scored by two people. This type of reliability, indeed, to measure the consistency of the test. So, there were two raters to examine the students’ composition. The raters must be in the same ability of writing knowledge. In this case, the first rater was the researcher, and the second rater was the researcher’s colleague who is also studying in English Education major and taking research course. Then, in order to analyze the reliability of the test, it was used Pearson Product Moment formula to know the correlation. The formula is as follows by using Pearson r (Bartz, 1976: 193): (1) In which: N : number of pairs of scores Σ X Y : sum of the product of each pair of scores Ẍ : mean of the X distribution Ÿ : mean of the Y distribution Sx : standard deviation of X distribution Sy : standard deviation of Y distribution The inter – rater reliability analysis, also showed that the instrument of tryout test was reliable. It is since the the instrument was considered consistent proved by the result of Pearson Product Moment analysis is 0.64 indicates the criteria of strong r (reliable). Since the tryout test instrument was valid and reliable, then it was used to be an instrument for pre-test and post-test. Scoring Guide To assess the students’ composition, the researcher used a scoring guide which is design by adopting Jacob et.al’s idea (1981) about testing ESL composition. The scoring guide assessed the students’ composition in some factors of writing that can be evaluated as explained by Madson (1983: 101). However in this case, the guidance only assesses the students’ composition in five writing areas that related to writing job application letter; those are content, organization, vocabulary, mechanics, and language use. Each of these components has different criterion and different point ranges. In using scoring guide, the raters should read the students’ composition first, and then decided the points to be computed become the total score. Data Collection Technique The data of this study was collected through the tests; tryout, pre – test and post – test; to investigate the students’ learning outcomes in writing a job application letter. The fist step, the researcher conducted tryout that is administered on Tuesday, 19th November 2013 in the 7th period to the students of XII AK 2. Then, before implementing the technique, the researcher administered pre – test to both experimental and control groups. Each students in both two groups were asked to write a job application letter with the instruction “Write an application letter to apply for a job based on job vacancy advertisement given” in 45 minutes time allocation. The test was the same with the tryout since the result of the tryout was valid and reliable. The pre-test was conducted to know the basic ability of the students in the beginning of the study. The pre-test was conducted on Wednesday, 20th November 2013 in the 2nd period to the control group, and in the fifth period to the experimental group. After administering pre – test, the researcher gave treatment to experimental group, but not to control group. The researcher taught writing job application letter to the experimental group by using Integrated Writing Technique, then asked them to compose job application letter in the end of meeting. Indeed, the topic of writing job application letter in the teaching and learning process was different from the topic in the pre-test and post-test. The treatment was conducted three times in which each treatment needed 45 x 2 minutes time allocation. The first treatment was conducted after administering pre-test on Wednesday, 20th November 2013 in the 6th and 7th period, the second treatment was conducted on Wednesday, 27th November 2013 in the 5th and 6th period, and the third treatment was conducted on Wednesday, 04th December in the 5th and 6th period. However, the control group was also taught by the teacher without using Integrated Writing Technique, but with the same material about writing job application letter through conventional way of teaching. The control group was also taught three times with 45 x 2 minutes time allocation in each meeting. The first meeting was conducted on Wednesday, 20th November 2013 in the 3rd and 4th period, the second meeting was conducted on Wednesday, 27th November in the 3rd and 4th period, and the third meeting was conducted on Wednesday, 04th December 2013 in the 2nd and 3rd period. Finally, the last step, the researcher conducted post – test for the both experimental and control groups. The purpose of this post – test was in order to know whether there is any significant difference in terms of writing job application letter learning outcomes between the experimental group and control group. The test that was used here was the same with the pre – test. So that the students both in experimental and control groups in this post-test were asked to make a job application letter based on the given job vacancy advertisement. The post-test was administered after the third treatment, that was on Wednesday, 04th December 2013 in the 4th period for control group, and in the 7th period for experimental group. Data Analysis Technique After tabulating the scores from pre – test and post – test of each group, the next step was that the scores were analyzed statistically by using procedure of analyzing t – test through SPSS. It since the result of the study was determined by comparison of pre – test and post – test, as McMillan (1992:197) stated that t-test is used to compare two means to see the level of significance for rejecting the null hypothesis. Pallant (2010) provided the procedures for analyzing t-test by using SPSS. From several number of different types of t-tests available in SPSS, the researcher used two types of t-test which were used in analyzing the data in this study; those are independent-samples t-test, and paired-samples t-test. Pallant (2010 : 239) stated that independent-samples t-test is used to compare the mean scores of two different groups of people or conditions, while paired-samples t-test is used to compare the mean scores for the same group of people on two different occasions, or to match pairs. In this study, independent-samples t-test was used to compare the mean score on the result of students’ compositions in pre-test and post-test, between experimental group and control group. Its aim is to know whether there is any significant difference in students’ writing ability between experimental group and control group in the pre-test and post-test. Besides, in analyzing the data of this study, the researcher also used paired-samples t-test to assess the result of the students’ composition in both pre-test and post-test for each of experimental and control group. Its aim is to know whether there is any development in the students’ writing skill after conducting the treatment and teaching and learning process. RESULT AND DISCUSSION The explanation of the statistical result showed that the main Alternative Hypotheses (H1) which stated that there is significant difference in learning outcomes of writing job application letter between students who are taught by integrated writing technique and those who are not is accepted. It since the result of Independent – samples t-test showed that in pre-test, the students scores of control group was higher than experimental group with their mean difference was (p) value = .105 with magnitude of difference was (.06) eta squared showed moderate effect size. Meanwhile, in post-test, although the mean scores of control group was still higher then experimental group, but their magnitude of difference was decreased. Their (p) value = .92 with (.0002) eta squared shows very small effect size; far smaller than their magnitude of difference in the pre-test. It is since based on the result of Paired – samples t-test analysis, the improvement of students’ writing job application letter learning outcomes or scores of experimental group is higher than control group. Paired – samples t-test showed that there is statistically significant increase of experimental group writing scores from pre-test to post-test with (p) value (.000), and the magnitude of improvement is (.52) eta squared (very large effect). While, the increase of control group writing composition scores is statistically considered has no significant increase from pre-test to post-test, since its (p) value is (.069). Although its magnitude of improvement is considered has large effect size with (.14) eta squared, but it is far smaller than the magnitude of improvement of experimental group. Thus, based on the result, it can be concluded that overall integrated writing technique is more effective than conventional way in improving the students learning outcomes in writing job application letter. The terms of content in writing composition of job application letter is knowledgeable of the content, means that the content or body of application letter is relevance to the assigned job vacancy advertisement. In this case, the students were asked to compose job application letter based on the job vacancy advertisement given. So that, the researcher investigate whether the content of the students job application letter composition is relevance with the information and requirements stated in the job vacancy advertisement or not. In the job vacancy advertisement given, the job position could be applied is Sales and Leasing Executives (S&LE) in Pakuwon Group. While the requirements for the applicants are; having 3 years experience in advertising, event organizer, sponsorship, or leasing space, having education background of minimum D3 in economy – management, marketing, or relevant major from reputable University, and must be fluent in English, having good appearance, and presentable. The result of analysis toward students writing ability in term of its content, also accept the Alternative Hypotheses (H1) which stated that there is significant difference in learning outcomes of writing job application letter in terms of contents between students who are taught by integrated writing technique and those who are not. The result of paired – sample t-test showed that there was significant increase of students’ writing job application letter learning outcomes in terms of content of experimental group. The increase magnitude is (.33) eta squared; indicates very large effect size with a substantial increase in the students’ composition scores in terms of content from pre-test to post-test. However, the scores of control group writing compositions in term of content was getting decrease from pre-test to post-test with magnitude of decrease (.05) eta squared indicates moderate effect size of decrease. So that, based on the result, it can be concluded that integrated writing technique is more effective than conventional way in improving the students’ learning outcomes in writing job application letter in term of its content. The term of organization in writing composition of job application letter consists of structure and sequence. A job application letter must be composed well organized and logically sequencing based on the correct form of job application letter. The body of job application letter must consist of first paragraph contains the applicants’ background, second paragraph contains the applicants’ qualification, final paragraph contains applicants’ interest, and closing paragraph consists applicants’ request for an interview that must be written sequencely. Besides, a job application letter must also has Return Address, Date, Addressee, Salutation, Body, Closing, and Signature). For students’ composition ability in term of its organization, statistical analysis concluded that the Alternative Hypotheses (H1) which stated that there is significant difference in learning outcomes of writing job application letter in terms of organization between students who are taught by integrated writing technique and those who are not is also accepted. The conclusion that is maintained from the result of paired – sample t-test which stated that the mean increase of students composition scores in term of organization of experimental group is higher than control group. The magnitude of increase of students composition score in experimental group is (.43) eta squared indicates very large effect size. While, the magnitude of increase of students composition scores in control group is only (.16) eta squared. Then, it can be concluded that integrated writing technique is more effective than conventional way in improving the students learning outcomes in writing job application letter in term of its organization. The term of vocabulary in the job application letter composition consists of word choice and usage, word form mastery, register. A good job application letter will be composed by using effective word choice and usage, good word form mastery, and appropriate register. Based on the result analysis and explanation toward students’ composition scores in term of its vocabulary, Alternative Hypotheses (H1) which stated that there is significant difference in learning outcomes of writing job application letter in terms of vocabulary between students who are taught by integrated writing technique and those who are not is also accepted. The conclusion is maintained from the result of paired – samples t-test which stated that the mean increase of students composition score in term of vocabulary of experimental group is higher than control group. The magnitude of increase of students’ composition in term of vocabulary in experimental group scores is (.18) eta squared indicates large effect size. While, the magnitude of increase of students’ composition in term of vocabulary in control group scores is only (.01) eta squared indicates small effect size. Then, it can also be stated that integrated writing technique is more effective than conventional way in improving the students learning outcomes in writing job application letter in term of its vocabulary. The term of language use in a job application letter composition means complex construction consists of tenses, number, word order or function, article, pronoun, and preposition. A good composition of job application letter is composed by using appropriate tenses, number, word order or function, article, pronoun, and preposition. However, the result of statistical analysis toward students’ composition scores in term of its language use rejected the Alternative Hypotheses (H1) which stated that there is significant difference in learning outcomes of writing job application letter in terms of language use between students who are taught by integrated writing technique and those who are not. It since the result of paired – samples t-test stated that the mean increase of students composition score in term of language use of control group is higher than experimental group. The magnitude of increase of students’ composition in term of language use of control group is (.41) eta squared indicates very large effect size. While, the magnitude of increase of students’ composition in term of language use of experimental group is only (.17) eta squared lower than control group. Thus, Null Hypotheses (H0) which stated that there is no significant difference in learning outcomes of writing job application letter in terms of language use between students who are taught by integrated writing technique and those who are not is accepted. The term of mechanic in writing composition of a job application letter means convention which contains of spelling, prepositions, punctuation marks, and capitalization. The well written job application letter is composed by using the correct spelling, prepositions, punctuation marks, and capitalization. The statistical analysis toward students’ composition scores in term of its mechanics also rejected the Alternative Hypotheses (H1) which stated that there is significant difference in learning outcomes of writing job application letter in terms of mechanics between students who are taught by integrated writing technique and those who are not. The result of paired – sample t-test showed that integrated writing technique was not effective in teaching writing job application letter in term of its mechanics. It since the students’ composition scores in term of mechanics for both experimental group and control group was getting decrease from pre-test to post-test. The mean decrease of experimental group is 0,091 with (.006) eta squared magnitude of decrease; while the mean decrease of control group is 0,609 with (.3) eta squared magnitude of decrease. CLOSING Conclusion After the result was obtained from conducting the research and analyzing the data, it can be concluded some conclusion: 1) Integrated Writing Technique is overall more effective than conventional way in improving the students learning outcomes in writing job application letter. It since the result of students’ composition total scores of experimental group was getting increase with magnitude of increase (.52) eta squared indicates very large effect size, higher than the increase of control group’s composition total score which only has magnitude of increase (.14) eta squared indicates large effect size. 2) Integrated Writing Technique is more effective than conventional way to improve the students learning outcome in writing job application letter in term of content, organization, and vocabulary. In term of content, the improvement of scores of students who were taught by using Integrated Writing Technique with magnitude of increase (.33) eta squared is higher than theirs who were not which only has magnitude of increase (.05) eta squared. In term of organization, the improvement of scores of students who were taught by using Integrated Writing Technique with magnitude of increase (.43) eta squared is higher than theirs who were not which only has magnitude of increase (.16) eta squared. In term of vocabulary, the improvement of scores of students who were taught by using Integrated Writing Technique with magnitude of increase (.18) eta squared indicates large effect size, higher than the increase of control group which only has magnitude of increase (.01) eta squared indicates small effect size. 3) In term of language use, Integrated Writing Technique is less effective than conventional way to improve the students learning outcome in writing job application letter. The improvement of scores of students who were taught by using Integrated Writing Technique with magnitude of increase (.17) eta squared indicates large effect size, lower than the increase of control group which has magnitude of increase (.41) eta squared indicates very large effect size. 4) The last, in term of mechanics, Integrated Writing Technique is not effective to improve the students learning outcome in writing job application letter. It is since in term of mechanics, the scores of students in both experimental and control group were getting decrease. The magnitude of decrease of experimental group is (.006) eta squared, while the magnitude of decrease of control group is (.3) eta squared. Suggestion The researcher would offer some suggestions to the next practitioners related to this study; comprises the next researchers and teachers. For the next researchers, it can be done research related to testing the effectiveness of integrated writing technique in teaching writing that focused on the other genres of text. Therefore, it can enrich the outcomes that hopefully could strengthen the result of the previous research by extending the focus on other writing genres. Or it can be research about the application of this technique to teach writing job application letter by using classroom action reasearch design. Then, for the teachers, the researcher suggests that the teachers would apply integrated writing technique to teach writing job application letter. It since this technique is proven effective to improve the students‘ writing job application letter ability; although only in terms of content, organization, and vocabulary. To improve the students’ learning outcomes in terms of language use and mechanics, the teacher could apply other additional technique combined with this technique. REFERENCES Abbott, Gerry and John Greenwood et al. (1981). The teaching of English as an International Language; A practical guide. Great Britain: William and Collins Sons and Co. Ltd. Ary, D., Jacobs, L. C., Sorensen, C., & Razavieh, A. (2010). Introduction to Research in Education. Belmont: Wadsworth Cengage Learning. B-Ikeguchi, C. (1997). Teaching Integrated Writing Skills. The Internet TESL Journal, III(3), 1-3. Bartz, A.E. (1976). Basic Statistical Concept in Education Behavioral Sciences. Minnesota: Burgess Publishing Company. Byrne, D. (1991). Teaching Writing Skill. London: Longman Group Ltd. Jacobs, H. L., Zinkgraf, S. A., Wormuth, D. R., Hartfiel, V. F., & Hughey, J. B. (1981). Testing ESL Composition: A Practical Approach. London: Newbury House Publishers, Inc. Kurniawan, Eri, & Kurniawan, Arief. (2008). Communication Builder English for Vocational School for Intermediate Level (Grade XII). Jakarta: Pusat Perbukuan Departemen Pendidikan Nasional. Madsen, H. S. (1983). Techniques in Testing. New York: Oxford University Press. Marczyk, G., DeMatteo, D., and Festinger, D (2005). Essentials of Research Design and Methodology. New Jersey: John Wiley & Sons, Inc. McMillan. James, H. And Sally Schumacher. 1992. Research in Education: A copcetual introduction. New York: Harper Collins College Publisher. Vidiana, N. (2012). The Effectiveness of Integrated Writing Technique in Teaching Writing Hortatory Exposition Text to the Eleventh Graders of SMA Negeri 13 Surabaya. Surabaya State University, Surabaya. Oshima, Alice, & Hogue, A. (2006). Writing Academic English. New York: Pearson Education. Pallant, Julie. (2010). SPSS Survival Manual. London: Open University Press. Pendidikan, B. S. N. (2006). Standar Isi untuk satuan Pendidikan Dasar dan Menengah Standar Kompetensi dan Kompetensi Dasar SMK/MAK. Jakarta: BSNP. Rass, R. A. (2001). Integrating Reading and Writing for Effective Language Teaching. English Teaching Forum, 39(1), 1-5. Rebecca, Oxford. (2001). Integrated Skills in the ESL/EFL Classroom. ESL Magazine, 6 (1). Shalabi, H. A., Al-Hashemi, R., & Al-Ramadin, T. A. (2013). Automatic Cover Letter Generator System from CVs (ACLGS). Global Journal of Computer Science and Technology, 13(3), 8. Smoak, R. (2003). What Is English for Specific Purpose? English Teaching Forum, 6. Susanto. 2000. Menyusun Usulan Penelitian Dan Laporan Penelitian. Surabaya: Universitas Negeri Surabaya. Wallace, R. (2006). Adams Cover Letter Almanac. Canada: Adams Media. Walsh, E. M. (1977). Teaching the Letter of Application. College Composition and Communication 28, 374-376. Retrieved from http://www.jstor.org/stable/356735 Yan, G. (2005). A Process Genre Model for Teaching Writing. English Teaching Forum, 43(3), 18-26. Yate, M. J. (2004). Cover Letter that Knock Them Dead. Avon: Adams Media.